Teologia i religioznawstwo: uwagi metodologiczne na marginesie monografii Krzysztofa Pilarczyka Biblia chrześcijan - Trzcionkowski, Lech (Przegla̜d religioznawczy, 2022)
The article aims to present methodological issues of the contemporary historical study of religion and studies of early Christianity as a historical phenomenon. The scientific study of religion uses the methodology appropriate for studying the products of human activity. Therefore, the anthropocentric history of religions examines human activity related to ideologies and activities claiming non-human origins. On the other hand, theology is permanently linked to religious ideology and, as such, is one of the objects of religious studies. Although religious people may perceive religious studies claims as offensive, respect for religious sensibilitie.